Complement activity is associated with disease severity in multifocal motor neuropathy. Issue 4 (August 2015) - Vlam, Lotte; Cats, Elisabeth A.; Harschnitz, Oliver; Jansen, Marc D.; Piepers, Sanne; Veldink, Jan Herman; Franssen, Hessel; Stork, Abraham C.J.; Heezius, Erik; Rooijakkers, Suzan H.M.; Herpers, Bjorn L.; van Strijp, Jos A.; et al.
Abstract : Objective: To investigate whether high innate activity of the classical and lectin pathways of complement is associated with multifocal motor neuropathy (MMN) and whether levels of innate complement activity or the potential of anti-GM1 antibodies to activate the complement system correlate with disease severity. Methods: We performed a case-control study including 79 patients with MMN and 79 matched healthy controls. Muscle weakness was documented with Medical Research Council scale sum score and axonal loss with nerve conduction studies. Activity of the classical and lectin pathways of complement was assessed by ELISA. We also determined serum mannose-binding lectin (MBL) concentrations and polymorphisms in the MBL gene ( MBL2 ) and quantified complement-activating properties of anti-GM1 IgM antibodies by ELISA. Results: Activity of the classical and lectin pathways, MBL2 genotypes, and serum MBL concentrations did not differ between patients and controls. Complement activation by anti-GM1 IgM antibodies was exclusively mediated through the classical pathway and correlated with antibody titers ( p < 0.001). Logistic regression analysis showed that both high innate activity of the classical pathway of complement and high complement-activating capacity of anti-GM1 IgM antibodies were significantly associated with more severe muscle weakness and axonal loss. Conclusion: High innate activity of the classical pathway of complement and efficient complement-activating properties of anti-GM1 IgM antibodies are determinants of disease severity in patients with MMN. These findings underline the importance of anti-GM1 antibody–mediated complement activation in the pathogenesis and clinical course of MMN.